miR-92 is a key oncogenic component of the miR-17-92 cluster in colon cancer - Tsuchida, Akihiko; Ohno, Shinichiro; Wu, Weihong; Borjigin, Nariso; Fujita, Koji; Aoki, Tastuya; Ueda, Shinobu; Takanashi, Masakatsu; Kuroda, Masahiko (Cancer science, 2011)
MicroRNAs (miRNAs) belong to a class of endogenously expressed non‐coding small RNAs that function primarily as gene regulators. Growing evidence suggests that miRNAs play a significant role in tumor development, making them potential biomarkers for cancer diagnosis and prognosis. The miR‐17–92 cluster has emerged as an important locus, being highly overexpressed in several cancers in association with cancer development and progression. The miR‐17–92 miRNA cluster generates a single polycistronic primary transcript that yields six mature miRNAs: miR‐17, miR‐18a, miR‐19a, miR‐20a, miR‐19b, and miR‐92a. In colon cancer development, the pathophysiologic roles of these transcripts and their targets are largely unknown. In the present study, we performed copy number analyses of the six miRNAs transcribed from the miR‐17–92 cluster in colon tumor tissues. We determined that miR‐92a was transcribed at higher levels than the other five miRNAs in both adenomas and carcinoma. In addition, miR‐92a directly targeted the anti‐apoptotic molecule BCL‐2‐interacting mediator of cell death (BIM) in colon cancer tissues. An anti‐miR‐92a antagomir induced apoptosis of colon cancer‐derived cell lines. These data indicate that miR‐92a plays a pivotal role in the development of colorectal carcinoma. (Cancer Sci 2011; 102: 2264–2271)